5x-3+x+12=9x-12

Simple and best practice solution for 5x-3+x+12=9x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3+x+12=9x-12 equation:


Simplifying
5x + -3 + x + 12 = 9x + -12

Reorder the terms:
-3 + 12 + 5x + x = 9x + -12

Combine like terms: -3 + 12 = 9
9 + 5x + x = 9x + -12

Combine like terms: 5x + x = 6x
9 + 6x = 9x + -12

Reorder the terms:
9 + 6x = -12 + 9x

Solving
9 + 6x = -12 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
9 + 6x + -9x = -12 + 9x + -9x

Combine like terms: 6x + -9x = -3x
9 + -3x = -12 + 9x + -9x

Combine like terms: 9x + -9x = 0
9 + -3x = -12 + 0
9 + -3x = -12

Add '-9' to each side of the equation.
9 + -9 + -3x = -12 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = -12 + -9
-3x = -12 + -9

Combine like terms: -12 + -9 = -21
-3x = -21

Divide each side by '-3'.
x = 7

Simplifying
x = 7

See similar equations:

| .1=0.2(x+2) | | 4.6x=14.2 | | (-2x-7)=87 | | X-(-10)forx=12 | | 3000=50(x) | | 2(1-3x)-8=-2(-5+4x) | | 3a+9b-3a-1b= | | 0.02(5000)+0.03=0.025(5000+x) | | 36k^2=60k+25 | | X+(10+x)=64 | | 2x+16+x+41=180 | | 7x-9=x-15 | | y=-2*-2+2*-2-7 | | 66x+20x=400+66x | | y=-2*-2+2-7 | | y=0*0+2*0-7 | | (66+20)x=400+66x | | n=-39-5m | | 2(2x+15)=190 | | 5x-4x+3=9-3 | | 8x-21+23x-16=180 | | -25+3x=-7 | | (9+22)9=(12+c)12 | | -3(x+2)+2(3x-3)=5 | | (5m-2)(5m+2)= | | -5(-8+8x)=-3+3x | | 66+20x=400+66x | | 3x^3-6x^2-15X+18=0 | | 66+20x=400+6x | | 5x-3+2x+5=9x+6 | | 3=1.2+-0.2y | | 14x^3-8x^2+18x= |

Equations solver categories